Choriocarcinoma Metastatic to the Kidney Presenting With Prolonged Amenorrhea and Flank Pain - Behnamfar, Fariba; Mohammadizadeh, Fereshteh; Hashemi, Leila; Sheikhalian, Somayeh (Reports of Radiotherapy and Oncology, 2015)
Introduction: Gestational choriocarcinoma usually occurs following an intrauterine pregnancy. We report a case of metastatic choriocarcinoma to the left kidney and lungs with long term intermittent amenorrhea and vaginal bleeding after a normal vaginal delivery. Case presentation: A 43-year-old rural woman presented with prolonged amenorrhea. Her last delivery was three years ago. She also complained of hematuria and left flank pain. Serum β-hCG level was considerably high. She underwent endometrial curettage. Pathologic examination of endometrial curettage specimen revealed choriocarcinoma. Ultrasound revealed enlarged uterus involved by an irregular mass with heterogenous echo pattern and extensive myometrial invasion. A mass with similar echo pattern was also evident in the left kidney. Computerized tomography confirmed the intrauterine mass and involvement of the left kidney. On chest X-ray, metastatic nodules were seen in both lungs and in the left retrocardiac space. The patient underwent 10 courses of chemotherapy (8 treatment courses and 2 courses for consolidation) with EMA-CO regimen (etoposide, methotrexate, actinomycin D, cyclophosphamide, and vincristine/oncovine). Following the fifth course of chemotherapy, she became pancytopenic and febrile. This condition was successfully managed with G-CSF, leukovorin and antibiotics. The patient is now well and still under the chemotherapy. Her serum β-hCG level has fallen to negative (3 IU/mL). Conclusions: Gestational trophoblastic diseases should be considered in the differential diagnosis of prolonged amenorrhea in patients of reproductive age with a history of prior pregnancy. Moreover, symptoms related to metastatic involvement such as hematuria and flank pain may be among the first clinical manifestations of choriocarcinoma.